WAKAMONO KOTOBA PADA VIDEO REPLAY LIVE DI KANAL YOUTUBE NIHONGO NO MORI - Alif Sarifuin; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study is to explain the forms and meanings of Wakamono Kotoba that appear in live replay videos on the Nihongo no Mori YouTube channel. Wakamono Kotoba is said to be a variety of language created by a particular group or community, used in everyday communication with meanings known only to that group. The implementation of Wakamono Kotoba occurs in both real and virtual life, such as on social media. Social media is a popular long-distance communication technology today, and YouTube is one of its platforms. On the YouTube platform, Wakamono Kotoba is used not only in conversational form but also in discussions, as presented in one of the contents by the Nihongo no Mori channel. The researcher used the observation and note-taking method to collect data for this study. First, the researcher observed three videos titled "JAPANESE SLANG || 「テカる！」," "JAPANESE SLANG || 「ボコる！」," and "JAPANESE SLANG || 日本の若者言葉!" on the Nihongo no Mori YouTube channel. Then, the researcher observed and recorded the data found, which were later analyzed for the formation processes and meanings. Subsequently, the data were described in a descriptive form. The results obtained from this study included 16 data points of Wakamono Kotoba with five different formation processes.Key Words: Wakamono Kotoba, Replay Live, Youtube